Hybrid Solar Cell and Wind Turbine Technology with Android-Based Control System for Electricity Needs of Shrimp Farmers in Pangkep Regency - Andi Muhammad Taufik; Moh.Ahsan S Mandra; Risma Haris; Syafiuddin Parenrengi; Andi Zulfikar Yusuf (International Journal of Scientific Multidisciplinary Research, 2024)
The implementation of hybrid solar cell and wind turbine technology can meet the electricity supply needs of shrimp farming partners by converting solar and wind energy into electrical energy. This reduces production costs related to electricity expenditures, as a significant portion is supplied by the hybrid solar cell and wind turbine technology. The sustainable design resulting from the application of hybrid solar cell and wind turbine technology enables the Tumampua shrimp farming group to become self-reliant and resilient in their electricity needs. This approach has the potential for mass application by other shrimp farming groups in Boriappaka Village, Pangkep Regency, fostering energy-independent communities and contributing to environmental protection and conservation